Sociedade, política, cultura e meio ambiente: subsídios ao planejamento socioambiental à comunidade indígena Boca da Mata, na terra indígena São Marcos - Roraima - Galdino, Lucio Keury Almeida (2017)
The indigenous cause in Brazilian territory, especially in the states that make up the Legal Amazon, awakens discussions, debates and scientific productions in the various fields of academic knowledge, while contextualizing the social, cultural, territorial and environmental issues of the various communities of this region. In this perspective, the State of Roraima is marked by astrong presence of indigenous peoples in the context of 32 Indigenous Lands (TI), where, according to the 2010 Census conducted by the Brazilian Institute of Geography and Statistics (IBGE), its absolute population Is 451,227 in habitants and of these 11.18% are indigenous, a national highlight because it presents a high percentage of Indians in one state. The aim of this thesis is to study the Boca da Mata indigenous community (CIBM), in the São Marcos Indigenous Land (TISM), and its inserted elements (the Indian, culture and environment) in order to understand the organization and appropriation in the Geographic space, with a focus on the development of subsidies to the socio-environmental planning of the community. The thesis was designed in 2011 to develop an extension project in the community that has a population, according to the Basic Health Unit - UBS / SESAI (2015), of 584 inhabitants in 140 families and is located north of Roraima And distant, approximately, 25 km of the municipality of Pacaraima and 195 km of Boa Vista (capital). The work developed a General Methodology of Research (MGP) that is divided into three moments: structural (planning the thesis summary); Theoretical (bibliographical research) and empirical (in loco research), where they involved the epistemological concepts of Rodriguez et al. (2004); Rodriguez e Silva (2013); Sotchava (1977); Tricart (1977); Christofoletti (1979); Gorayeb, Mereles and Silva (2015); Fitz (2010); Martinelli (2011); among others. PPTAL / FUNAI techniques (2004) were used for structured and semi-structured interviews and systematic observation, in addition to the appropriate techniques applied to the thesis itself in data collection; Bibliographic research; Application of questionnaires; Analysis of satellite images and mapping. In the development of the thesis, the social, political, cultural and environmental contexts of the State of Roraima, as well as the environmental and social diagnosis of the area of study, were fundamental to expose the set of information (maps, Tables and tables) of the work that developed subsidies to the socioenvironmental planning of the indigenous community. It is well known that the indigenous struggle in Roraima has resurfaced strongly in the last decades and its history is marked by continuous processes of obstacles and conquests regarding the demarcation and homologation of the indigenous lands, the rescue and the preservation of their culture and the environment. It should be pointed out that the problems related to the social, economic and cultural development of traditional communities are intrinsically linked to public policies that are responsible for improving the quality of life of the inhabitants, including indigenous people.